Subcellular Cadmium, Lead and Mercury Compartmentalization in Guiana Dolphins (Sotalia guianensis) From Southeastern Brazil - Hauser-Davis, Rachel Ann; Figueiredo, Lívia; Lemos, Leila; de Moura, Jailson Fulgêncio; Rocha, Rafael C. C.; Saint’Pierre, Tatiana; Ziolli, Roberta L.; Siciliano, Salvatore (Frontiers in Marine Science, 2020)
Marine mammals are considered excellent ocean health sentinels and are ubiquitously exposed to chemical contaminants worldwide. The Guiana dolphin (Sotalia guianensis) is a near-threatened dolphin species from Brazil with unknown population size data. This indicates the need for assessments regarding deleterious effects that may arise from exposure to chemical contamination, especially metals. After entry in the organism, these compounds are subject to internal subcellular compartmentalization, which in turn alters their bioavailability. However, almost no assessments regarding subcellular metal contents in marine mammals are available. In this context, metal compartmentalization was determined in three subcellular fractions for three toxic elements, Cd, Hg and Pb, by inductively coupled plasma mass spectrometry (ICP-MS) in Guiana dolphin kidney and liver samples from Southeastern Brazil. Differential metal-detoxification mechanisms were observed for the three elements, where metallothionein (MT) detoxification was postulated for only for Pb, while Cd and Hg were poorly associated to MT, and mostly present in the insoluble fraction, indicating low bioavailability. This is the first report on subcellular metal compartmentalization in Guiana dolphins and indicates that critical biochemical detoxification data is obtained through subcellular fraction analyses in marine mammals. This indicates an emerging study field for this type of assessment, which may, in turn, aid in conservation efforts.